Use the image to answer the question.

Two lines slope upward on a coordinate plane. A solid line passes through the plotted point left parenthesis 2 comma 7 right parenthesis. A dotted line intersects the first line at the plotted point left parenthesis negative 1 comma 1 right parenthesis.

What is the system of equations shown in the graph?

(1 point)
Responses

{y=2x−3y=3x−4
enlraged left brace start layout first row y equals 2 x minus 3 second row y equals 3 x minus 4 end layout

{y=−x+1y=2x+7
enlarged left brace start layout first row y equals negative x plus 1 second row y equals 2 x plus 7 end layout

{y=2x+3y=3x+4
enlarged left brace start layout first row y equals 2 x plus 3 second row y equals 3 x plus 4 end layout

{y=3x+2y=4x+3

1 answer

To determine the correct system of equations, let's analyze the information given from the description you've provided:

  1. Solid line that passes through the point (2, 7).
  2. Dotted line intersects the first line at the point (-1, 1).

To find the equations of the lines, we can use the point-slope form of a linear equation, \(y = mx + b\), where \(m\) is the slope and \(b\) is the y-intercept.

Given that we have two points for the solid line, (2, 7) and presumably another point that we can derive from the intersection (intersecting with the dotted line at (-1, 1)), we need to find the slopes.

  1. For the solid line that passes through (2, 7):

    • We can determine the slope with another point (if there were any given or assumed).
  2. For the dotted line intersecting at (-1, 1):

    • Its slope can also be determined if we had another point.

Now we can work through the options provided to see which one fits these conditions.

Let's Analyze the Options:

  1. Option 1: \[ \begin{align*} y &= 2x - 3 \ y &= 3x - 4 \end{align*} \]

    • Check (2, 7) in the first equation: \(7 = 2(2) - 3\) => \(7 = 4 - 3\) => no, does not work.
  2. Option 2: \[ \begin{align*} y &= -x + 1 \ y &= 2x + 7 \end{align*} \]

    • Check (2, 7) in second equation: \(7 = 2(2) + 7\) => \(7 = 4 + 7\) => no, does not work.
  3. Option 3: \[ \begin{align*} y &= 2x + 3 \ y &= 3x + 4 \end{align*} \]

    • Check (2, 7) in the first equation: \(7 = 2(2) + 3\) => \(7 = 4 + 3\) => yes, works!
    • Now for the other point (-1, 1): Check in second equation: \(1 = 3(-1) + 4\) => \(1 = -3 + 4\) => yes, works!
  4. Option 4: \[ \begin{align*} y &= 3x + 2 \ y &= 4x + 3 \end{align*} \]

    • Check (2, 7) in the first equation: \(7 = 3(2) + 2\) => \(7 = 6 + 2\) => no, does not work.

Conclusion:

From the analysis, Option 3 is the correct system of equations.

\({ y = 2x + 3, y = 3x + 4 }\)